The Analysis of Lamongan Toddler Nutrition Care (PELITA LA) Program in Dradah Health Center Lamongan - Rahmawati, Aulia Firda; Husodo, Besar Tirto; Handayani, Novia (Journal of Public Health for Tropical and Coastal Region, 2021)
Introduction: The prevalence of stunting in Lamongan is reaching 35,5%, so the efforts to reduce the prevalence of stunting in Lamongan was implementing the Lamongan Toddler Nutrition Care program. There is no evidence of the successes of that program. The purpose of this study is to analyze the process of the Lamongan Toddler Nutrition Care (PELITA LA) program on stunting in Lamongan, East Java.Methods: This research uses qualitative methods with in-depth interview data collection techniques and includes descriptive research. The sample of this research is 5 respondents who are selected using purposive sampling. This research has been approved as ethical by the ethics committee. The process of data analysis in this study starts by collecting data from the interview results and then reducing the data that has been generated. After that, the data are presented and concluded.Result: The results showed that not all the the village health workers had received training, the infrastructure was insufficient and there were no program implementation guidelines so can influence prevalence stunting. However, the process of management like planning, organizing, actuating, and controlling have been good. In another statement about the successes of the program is decreasing the prevalence of the stunting and increasing the participants’ knowledge but the participants are not measured with certainty to find out their knowledge.Conclusion: The conclusion is the nutrition care program for Lamongan toddlers at the Lamongan Health Center has not been running optimally because the input and output aspects have not been going well